Use of Mineral Trioxide Aggregate in the Treatment of Horizontal Root Fractures with a 5-Year Follow-up: Report of a Case - GENÇOĞLU, NİMET (ELSEVIER SCIENCE INC, 2009)
Root fractures are those that involve dentin, cementum, and the pulp. They occur more frequently in children than adults. This case report describes the treatment and 5-year follow-up of two maxillary central incisors with horizontal root fractures using mineral trioxide aggregate and the application of intracoronal bleaching of the discolored tooth. (J Endod 2009;35:292-295)
Keywords: Apical plug; follow-up; mineral trioxide aggregate; root canal treatment; root fracture; RESISTANCE; TEETH; MTA